Intestinal Microbiota of Broiler Chickens As Affected by Litter Management Regimens - Wang, Lingling; Lilburn, Mike; Yu, Zhongtang (Frontiers in Microbiology, 2016)
Poultry litter is a mixture of bedding materials and enteric bacteria excreted by chickens, and it is typically reused for multiple growth cycles in commercial broiler production. Thus, bacteria can be transmitted from one growth cycle to the next via litter. However, it remains poorly understood how litter reuse affects development and composition of chicken gut microbiota. In this study, the effect of litter reuse on the microbiota in litter and in chicken gut was investigated using 2 litter management regimens: fresh vs. reused litter. Samples of ileal mucosa and cecal digesta were collected from young chicks (10 days of age) and mature birds (35 days of age). Based on analysis using DGGE and pyrosequencing of bacterial 16S rRNA gene amplicons, the microbiota of both the ileal mucosa and the cecal contents was affected by both litter management regimen and age of birds. Faecalibacterium, Oscillospira, Butyricicoccus, and one unclassified candidate genus closely related to Ruminococcus were most predominant in the cecal samples, while Lactobacillus was predominant in the ileal samples at both ages and in the cecal samples collected at day 10. At days 10 and 35, 8 and 3 genera, respectively, in the cecal luminal microbiota differed significantly in relative abundance between the 2 litter management regimens. Compared to the fresh litter, reused litter increased predominance of halotolerant/alkaliphilic bacteria and Faecalibacterium prausnitzii, a butyrate-producing gut bacterium. This study suggests that litter management regimens affect the chicken GI microbiota, which may impact the host nutritional status and intestinal health.